2014
DOI: 10.1210/jc.2014-2550
|View full text |Cite
|
Sign up to set email alerts
|

Breast Adipose Tissue Estrogen Metabolism in Postmenopausal Women With or Without Breast Cancer

Abstract: Estrogen metabolism is differentially regulated in the adipose tissue of women with or without cancer. In the sc adipose tissue proximal to breast tumor 17β-hydroxysteroid dehydrogenase type 12 expression is lower than in controls, which could indicate that the conversion of estrone to estradiol is decreased. Further studies are needed to establish the clinical significance of our findings in the development and growth of breast cancer in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 37 publications
1
30
5
1
Order By: Relevance
“…The majority of human studies have been conducted in breast cancer patients (n=7) (66,68,70,7578). Other studies have been implemented in cancers of the gastrointestinal tract (colorectal cancer (n=4) (8,64,71,73), esophageal cancer (n=2) (65,79), combined (colorectal and esophageal) (n=1) (80)), reproductive cancer (endometrial (n=1) (72), prostate (n=4) (69,74,81,82)), or ENT tract (tongue (n=1) (83)).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of human studies have been conducted in breast cancer patients (n=7) (66,68,70,7578). Other studies have been implemented in cancers of the gastrointestinal tract (colorectal cancer (n=4) (8,64,71,73), esophageal cancer (n=2) (65,79), combined (colorectal and esophageal) (n=1) (80)), reproductive cancer (endometrial (n=1) (72), prostate (n=4) (69,74,81,82)), or ENT tract (tongue (n=1) (83)).…”
Section: Resultsmentioning
confidence: 99%
“…Of interest, while the risk for breast cancer is increased for obese postmenopausal women, premenopausal obese women have a lower incidence of breast cancer (84). Adipocytes comprise about 90% of the normal breast tissue and thus, the question of adipocytes contributing directly to tumor progression as part of the tumor stroma has been addressed in several studies (66,68,70,75,76). Breast cancer stroma can be classified into adipose stroma cancer (>50% of cells are adipocytes), and fibrous stroma cancer (100% of cells are fibroblasts) or a combination of both stroma types (<100% of cells are fibroblasts, <50% are adipocytes) (76).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, both breast cancer cells and adipocytes play an important role in inducing aromatase in carcinoma cells and stromal cells at the breast cancer invasion front [70]. In contrast, a recent study revealed lower estradiol production in adjacent adipose tissue of estrogen receptor positive post-menopausal breast cancer patients compared to the adipose tissue of patients with breast reduction mammoplasty, while serum concentrations did not differ [71]. Although these studies were preliminary, not always age-and/or body mass index (BMI)-matched, and performed on only small groups of patients, making it hard to draw definite conclusions, they indicate that breast cancer cells can influence local adipose tissue hormone production and vice versa.…”
Section: Adipose Tissue and Hormone Metabolismmentioning
confidence: 95%
“…Végül a 4-hidroxi-ösztrogének az öszt-rogénreceptorokhoz kapcsolódva aktiválják az ER mediálta jelátviteli útvonalakat, ezzel iniciálva a DNS-károsító mechanizmusokat. Mivel az egyes folyamatok a szöveti mikrotérben, igen kis mennyiségű vegyület részvételével játszódnak le, a szisztémás ösztradiolszintek mérése az ösztrogénhatással összefüggő kórfolyamatok korai diagnózisában és monitorozásában nem elégséges [34].…”
Section: Az öSztrogénmetabolitok Biológiai Hatásaiunclassified